Oxytocin Level and Breast Engorgement In Primipara Mother with Postpartum Blues - Sugeng, Ika Larasati (Jurnal Ners, 2017)
Introduction: Postpartum is a great moment for most the woman, but for some of them is a frightening moment. Postpartum blues makes woman avoiding their baby. Whereas lactation process needs to be done in early postpartum period. The aim of this study is analyzing the oxytocin level and breast engorgement incident in primipara mother with postpartum blues in Obtetry & Gynecology Department of Dr. M Soewandhie Hospital of Surabaya. Methods: This study was used cross sectional design. Population were primiparas and samples were 41 primiparas choosen by random sampling according to inclusion criteria. The independent variable was postpartum blues, dependent variables were breast engorgement and oxytocin level. The instruments used were Kennerly & Gath Postpartum Scale, and Six-point Engorgement Scale. Data were analyzed with Spearman Test and Mann Whitney Test using α<0,05. Result: The result shown that the oxytocin level change comparing the postpartum blues in p=0,002 and increasing breast engorgement incident comparing to postpartum blues in p=0,000. Conclusion: There was difference of oxytocin level between postpartum blues mother and not postpartum blues mother and increasing of breast engorgement incident to postpartum blues mother comparing to not postpartum blues mother. Dr. M. Soewandie hospital of Surabaya needs to arrange a standard in service of treating laboring mother in case of reducing stress during delivery process and manage ward situation comfortly.